2014
DOI: 10.1098/rspb.2013.1979
|View full text |Cite
|
Sign up to set email alerts
|

The role of ecological opportunity in shaping disparate diversification trajectories in a bicontinental primate radiation

Abstract: Exceptional species and phenotypic diversity commonly are attributed to ecological opportunity (EO). The conventional EO model predicts that rates of lineage diversification and phenotypic evolution are elevated early in a radiation only to decline later in response to niche availability. Foregut fermentation is hypothesized to be a key innovation that allowed colobine monkeys (subfamily Colobinae), the only primates with this trait, to successfully colonize folivore adaptive zones unavailable to other herbivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 80 publications
(100 reference statements)
2
18
0
Order By: Relevance
“…Derryberry et al. () found constrained morphological evolution in the radiation of Furnariidae, Tran () detected a possible lack of ecological opportunity in the radiation of African colobine monkeys, and Zelditch et al. () found that geography is a very important component in the speciation of diverse and rapidly diversifying continental squirrels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Derryberry et al. () found constrained morphological evolution in the radiation of Furnariidae, Tran () detected a possible lack of ecological opportunity in the radiation of African colobine monkeys, and Zelditch et al. () found that geography is a very important component in the speciation of diverse and rapidly diversifying continental squirrels.…”
mentioning
confidence: 99%
“…Other studies on continental radiations have shown a more varied relationship between adaptive divergence and ecological opportunity. Derryberry et al (2011) found constrained morphological evolution in the radiation of Furnariidae, Tran (2014) detected a possible lack of ecological opportunity in the radiation of African colobine monkeys, and Zelditch et al (2015) found that geography is a very important component in the speciation of diverse and rapidly diversifying continental squirrels. At continental scales, patterns of species and morphological diversification are sometimes found to be decoupled, leading, for instance, to clades with high species diversity but limited ecological variability (Kozak et al 2006;Burbrink et al 2012).…”
mentioning
confidence: 99%
“…Primates is one of the largest (>400 species), most ecologically diverse, socially complex, and broadly distributed orders of mammals (Lefebvre et al 2004;Dunbar and MacDonald 2013;Fahy et al 2013;Tran 2014). As a consequence, considerable interest has been placed in how Primates have diversified and the factors contributing to the uneven distribution of species diversity across its major clades (Fabre et al 2009;Stadler 2011;Springer et al 2012).…”
mentioning
confidence: 99%
“…For example, ecological opportunity does not always lead to a classic early burst of both diversification and divergence (Burbrink et al ), even when clades share the same sources of ecological opportunity (Burbrink et al ). Also, key innovations that confer ecological opportunity need not increase diversification rates (Claramunt et al ), even when disparity is elevated (Alfaro et al ; Dornburg et al ), and may even depress diversification (Tran ). Fourth, a link between diversification and divergence is not expected for some kinds of radiations, especially those termed “nonadaptive,” in which diversification is not accompanied by niche divergence (Gittenberger ; Wilke et al ); consequently, nonadaptively radiating clades are diverse but not disparate (e.g., Kozak et al ; Rowe et al ; Smith et al ).…”
mentioning
confidence: 99%